1969
DOI: 10.1039/j39690001353
|View full text |Cite
|
Sign up to set email alerts
|

Thiele acetylation of quinones. Part III. p-Benzoquinones with bromo- and methoxy-substituents

Abstract: The three monobromo-monornethoxy-p-benzoquinones have been prepared ; they all undergo Thiele acetylation.The entering acetoxy-group is found orrho or para to the bromine atom in each of the triacetates. and never ortho to the methoxy-group.Thiele acetylation of the three isomeric dibromo-rnonomethoxy-p-benzoquinones and the three monobrornodirnethoxy-p-benzoquinones has been studied. Of these six compounds the only two which undergo the reaction are 2.6-dibrorno-3-rnethoxyand 2-bromo-5.6-dimethoxy-p-benzoquin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Thus, 9 was synthesised in accordance with a literature procedure in three steps. 7 Close independent examination of the 1 H NMR of 7 and 9 showed that each was a pure regioisomer. However, when equimolar quantities of 9 and enamino ester 8 were dissolved in methanol at room temperature a remarkable transformation took place.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 9 was synthesised in accordance with a literature procedure in three steps. 7 Close independent examination of the 1 H NMR of 7 and 9 showed that each was a pure regioisomer. However, when equimolar quantities of 9 and enamino ester 8 were dissolved in methanol at room temperature a remarkable transformation took place.…”
Section: Resultsmentioning
confidence: 99%
“…Except for the known 1b , 25 each of the bromoquinone starting materials was prepared according to the literature. 2-Bromo-5,6-dimethylbenzoquinone ( 1a ) 26 was prepared by oxidation of the known hydroquinone.…”
Section: Resultsmentioning
confidence: 99%
“…2-Bromo-5,6-dimethylbenzoquinone ( 1a ) 26 was prepared by oxidation of the known hydroquinone. 17 2-Bromo-5-methoxybenzoquinone ( 1c ) and 2-bromo-6-methoxybenzoquinone ( 1d ), were prepared according to Blatchly et al 25 and 2-bromojuglone methylether 1e was prepared according to Jung. 27 Quinone 1b was prepared by AgO oxidation of known compound 11 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations